Industrial amino acids in diets for piglets and growing pigs - Inborr, J.; Suomi, K. (Agricultural and Food Science, 1988)
Two production trials with piglets and one with slaughter pigs were carried out in order to investigate the effects of reducing the protein content in the diets followed by an addition of industrial amino acids on performance and health status. In the first piglet trial the crude protein content of the control diet was decreased from 20 to 18.3 % and in the second from 18.3 to 16.7 %. In the trial with growing pigs, the protein content of the control diet was decreased from 17.0 to 15.5 %. Industrial L-lysine, DL-methionine and L-threonine were added to the low protein diets to get the same levels of these amino acids as in the control diets. Piglet performance was similar on all treatments indicating equal availability of added and protein-bound amino acids. Health status of piglets on the low protein diets was considerably improved, indicating less predisposition to post weaning diarrhoea. Pigs on the low protein amino acid fortified diet tended to gain weight faster (788 vs. 743 g/day; p<0.07) and had higher carcass quality than pigs on the control diet. Feed utilization was improved by 4 % on the low protein diet, although, the improvements were not significant.